Analysis of the Effect of Training, Work Discipline and Leadership on Employee Performance (Study of Security Guards at Surabaya State University) - Sundjoto, Sundjoto (Dinasti Publisher, 2023)
This study aims to analyze the effect of job training, work discipline, and leadership simultaneously on employee performance. Data was taken from 30 people who were sampled from 80 security guardsThe sampling method used is Probability sampling, the sampling technique used is simple random sampling. by distributing questionnaires to the respondents. Data analysis techniques use multiple linear regression analysisThis study uses validity test, reliability test, and classic assumption test with the help of SPSS 23.0. The results of this study indicate that the independent variables namely training (X1), work discipline (X2), leadership (X3) have a positive and significant effect on employee performance (Y).